Understanding Indicators of Talent Acquisition and Retention of Different Generations in Building Talent Management: A Case Study of DKI Jakarta Provincial Government - Septiana Dwiputrianti; Wahyu Sutiyono; Adi Suryanto; Tutik Rachmawati; Caesar Octoviandy Purba (Indonesian Association for Public Administration, 2023)
Talent management is important to obtain a professional, high-performance, and reliable apparatus. However, there are still very few studies on implementing talent management at the local government level in Indonesia. This paper aims to explain indicators of talent acquisition and retention of different generations in providing an understanding of implementation talent management, a case study in DKI Jakarta Provincial Government. Due to the regulation related to Talent Management for government institutions that were just issued, all government agencies have to implement talent management. However, there still needs to be a greater understanding of indicators for implementing talent acquisition and retaining talent (talent retention) to prepare future organizational leaders. This study applied mixed, qualitative, and quantitative approaches—a case study of the special capital region (DKI) Jakarta Provincial Government as a capital city. Respondents and informants total 43 officials from the DKI Jakarta Provincial Government. This study found that more than 90 percent of respondents agreed and strongly agreed with the indicators representing talent acquisition and retention. These findings are convinced by supporting data and information based on interviews and document implementation at DKI Jakarta Province. Furthermore, this study found a positively correlated relationship between talent acquisition and talent retention based on indicators of talent management implemented in DKI Jakarta Province. Therefore, this study's talent acquisition and retention indicators significantly contribute to local governments' understanding of implementing talent management policies and to the literature on talent acquisition and retention indicators for local government, especially in the Indonesian context.